Nonlinear Static Soil-Structure Interaction Analysis of Time-Dependent Soil Deformation Effects on RC Structures - Ayat Errahmane Remadna; Kamel Bezih; Rafik Demagh; Mohamed Saddek Remadna (The Journal of Engineering and Exact Sciences)
Soil response and superstructure behavior are two major factors influencing the long-term performance of reinforced concrete (RC) structures. Maintaining the structural integrity of these structures over time is crucial due to the complex static interactions between the soil and the structure. This study uses a finite element model to examine the stability of RC structures, considering the long-term static interactions between the nonlinear behavior of the soil and the structure. Numerical simulations are performed on real RC beam constructions at serviceability limit states (SLS) under various loading scenarios in both homogeneous and heterogeneous soil conditions. The parametric study's results indicate that soil heterogeneity and static soil-structure interactions significantly influence the design of RC structures. The nonlinear behavior of the soil over time intensifies these impacts further. This study shows how important it is to think about different types of soil and how they interact with structures when they are not moving. This is especially true when it comes to soil that is easily compressed and changes shape over time in a nonlinear way. By incorporating these factors, the research highlights the critical need to integrate soil heterogeneity and static interaction into the design process to ensure the stability and safety of RC structures. Ultimately, the results demonstrate that accounting for these complex interactions can greatly improve the durability and reliability of RC structures in diverse soil conditions.